1996
DOI: 10.1046/j.1468-2982.1996.1606436.x
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium in the Prophylaxis of Migraine—a Double-Blind, Placebo-Controlled Study

Abstract: The migraine prophylactic effect of 10 mmol magnesium twice‐daily has been evaluated in a multicentre, prospective, randomized, double‐blind, placebo‐controlled study. Patients with two to six migraine attacks per month without aura, and history of migraine of at least 2 years, were included. A 4‐week baseline period without medication was followed by 12 weeks of treatment with magnesium or placebo. The primary efficacy end‐point was a reduction of at least 50% in intensity or duration of migraine attacks in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
124
1
4

Year Published

2000
2000
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 175 publications
(131 citation statements)
references
References 24 publications
2
124
1
4
Order By: Relevance
“…This side effect seems to occur only with oral intake of magnesium, as we did not encounter any gastrointestinal side effects in our study with intravenous MgSO 4 [43], nor did Mauskop et al in a similar study [44]. Our total frequency of side effects with magnesium (47.8%) is comparable to that in other studies which reported frequencies of 37.2% [21] and 45.7% [20]. Our higher rate of side effects might result from the higher doses of magnesium we used.…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…This side effect seems to occur only with oral intake of magnesium, as we did not encounter any gastrointestinal side effects in our study with intravenous MgSO 4 [43], nor did Mauskop et al in a similar study [44]. Our total frequency of side effects with magnesium (47.8%) is comparable to that in other studies which reported frequencies of 37.2% [21] and 45.7% [20]. Our higher rate of side effects might result from the higher doses of magnesium we used.…”
Section: Discussionsupporting
confidence: 78%
“…Diarrhea was only seen in 1 patient (4%). This number is somewhat higher than in the studies of Pfaffenrath et al [20] (28.6%) and of Peikert et al [21] (18.6%), but in the latter study 2 patients (5%) had to discontinue treatment because of diarrhea [21]. This side effect seems to occur only with oral intake of magnesium, as we did not encounter any gastrointestinal side effects in our study with intravenous MgSO 4 [43], nor did Mauskop et al in a similar study [44].…”
Section: Discussioncontrasting
confidence: 59%
See 3 more Smart Citations